2022
DOI: 10.1136/bjo-2022-321815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spectacle lenses with aspherical lenslets on choroidal thickness in myopic children: a 2-year randomised clinical trial

Abstract: ObjectiveSpectacle lenses with highly aspherical lenslets (HAL) and slightly aspherical lenslets (SAL) showed effective myopia control. This study was to investigate their effects on macular choroidal thickness (ChT) in myopic children.MethodsExploratory analysis from a 2-year, double-masked, randomised trial. 170 children aged 8–13 years with myopia between −0.75D and −4.75D, astigmatism of 1.50D or less, and anisometropia of 1.00D or less were recruited. Participants were randomly assigned in a 1:1:1 ratio t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…This is important because the magnitude of the observed changes, particularly with two drops of cyclopentolate, was comparable to the ChT changes seen during myopia management. 7,11 Choroidal thinning following the instillation of cyclopentolate was similar in the atropine and placebo treatment groups, suggesting that the short-term effects of cyclopentolate were independent of long-term myopia management. To the contrary, 1% tropicamide did not produce any significant changes in ChT following cycloplegia, relative to the testretest ChT changes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This is important because the magnitude of the observed changes, particularly with two drops of cyclopentolate, was comparable to the ChT changes seen during myopia management. 7,11 Choroidal thinning following the instillation of cyclopentolate was similar in the atropine and placebo treatment groups, suggesting that the short-term effects of cyclopentolate were independent of long-term myopia management. To the contrary, 1% tropicamide did not produce any significant changes in ChT following cycloplegia, relative to the testretest ChT changes.…”
Section: Discussionmentioning
confidence: 88%
“…Therapies such as orthokeratology, management spectacles and atropine eye drops all produce effects on ChT. [7][8][9]11 Although the site action for atropine in myopia control remains unresolved, 32 recent evidence suggests that atropine's myopia control effect may be correlated with changes in ChT. 11 Consequently, ChT has been proposed as a useful biomarker in gauging long-term myopia control treatment.…”
Section: Subfoveal Region Subfovealmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that when their effects are integrated over time, the MS spectacles are successful in reducing the rate of myopia progression. The finding by Zhang et al 26 that the pattern of peripheral refraction in children who have worn MiyoSmart lenses differed from that of children wearing a SV correction emphasises the importance of the periphery in this process, although Huang et al 27 also found central changes in choroidal thickness after 2 years of Stellest wear.…”
Section: F I G U R Ementioning
confidence: 99%
“… 235 237 Measurements of choroidal thickness up to a month (1–4 weeks) following the initiation of optical myopia control treatments in myopic children have captured significant increases in choroidal thickness associated with a number of optical, myopia control treatments compared to children in traditional single-vision myopia correction, 237 241 with evidence of sustained effects (i.e., thicker choroid) over 12 to 24 months of treatment in some cases. 235 , 239 , 240 Furthermore, in the case of orthokeratology, the change in choroidal thickness after 1 month of lens wear was found to be associated with the degree of axial elongation observed over 12 months, suggesting that the shorter-term 1-month choroidal responses may be predictive of myopia control efficacy. 239 Both increased light exposure (i.e., outdoor time) and red light therapy have also been associated with long-term increases in choroidal thickness, 228 although the initial short-term response (1–2 hours) appears to be choroidal thinning.…”
Section: Implications Of Choroidal Thickness Modulation For Efficacy ...mentioning
confidence: 99%